Comparison of Bracket Position Accuracy with Different CAD/CAM Indirect Bonding Systems - Albertini, Paolo (2021)
Objective: To evaluate the accuracy of three different digital bracket positioning systems, comparing vertical, mesiodistal and buccolingual accuracy. Material and Methods:  The same case was sent to Orapix, Insignia, and Orthocad systems and the brackets were bonded to the malocclusion models. Damon 3 MX brackets were used with all systems and the brackets were bonded to the models with the same bonding protocol and materials. The comparison of the position of each single bracket was made with digital photography, and ImageJ software was used to find the length in pixels and then convert it to hundredths of a mm for vertical, mesiodistal and buccolingual displacement, compared to the setup. Results: Insignia System reported the average higher vertical displacement (0.28 mm), compared with the other two appliances (0.22-0.23 mm), and showed the lowest average displacement for the mesiodistal and buccolingual positioning (0.14 and 0.07 mm, respectively). However, these slight bracket positioning variations between these bonding systems were not statistically different (p>0.05). Conclusion:  The three systems analyzed were shown to be accurate in positioning the brackets, and none of them was statistically better.